Interannual eddy variability in the eastern Ryukyu Island chain - Zhang, Zhen-Long; Nakamura, Hirohiko; Kako, Shin’ichiro; Zhu, Xiao-Hua (Frontiers in Marine Science, 2023)
Interannual eddy variability in the eastern Ryukyu Island chain (RIC) was analyzed based on eddy trajectories and assimilation data. Analysis of the eddy trajectory data suggested a predominance of eddies originating near the study area. The occurrence frequency of eddies has interannual variability, but it demonstrates a different tendency with eddy kinetic energy (EKE): few eddies appear when EKE is high; however, they are strong with fast rotation speeds and increase in size. The EKE variability was correlated with the baroclinic conversion rates, suggesting a vital role of baroclinic instability in the study area. Baroclinic instability was found to be affected by the North Equatorial Current (NEC), during which more NEC water entered the eastern RIC, intensifying the vertical velocity shear between the upper and lower oceans. Consequently, baroclinic instability in the study area was enhanced.